Study on the relationship between Malaysian IPOs offer price with return IPOs in main board, second board and both board during financial crisis / Juhaimy Ishak (Faculty of Business and Management, 2006)
This study is undertaken to examine IPOs offer price and IPOs return in Main Board, in Second Board and Both Board from the Malaysia perspective. This study further examines the relationship between Malaysian IPOs offer price and IPOs return in Main Board, in Second Board and Both Board This study was done because of the Initial Public Offerings has important influence whereby company raises capital by issuing shares to investor to raises capital on life business and this area has not been greatly researched in Malaysia. All the data used are in monthly basis range from year 1997 until year 1999. In analyzing the data, Simple Linear Regression Model is used. The major findings of this study indicate that that all return IPOs in Main Board, in Second Board and Both Board have significant relationship with IPOs offer price.